Analysis Of The Physical Condition Of Male Sepak Takraw Athletes 2024 Central Java - Hartono, Winda; Wicaksono, Anggit (Journal of Sport Science and Fitness, 2025)
This study aims to find out how the physical condition of PON Central Java men's sepak takraw athletes is and as a benchmark or minimum standard for sepak takraw athletes who want to become national athletes. The type of research is Quantitative Research with a Descriptive Approach. The sample extraction technique uses a saturated sample technique, so that the research sample amounted to 10 athletes equal to the population. The population in this study is Central Java sepak takraw training athletes. The variables of the study are the physical condition of the athlete which consists of: 1) leg power 2) strength, 3) agility, 4) speed, and 5) aerobic endurance.  The five physical components were measured using valid and reliable instruments. The data used is secondary data obtained from the head coach of the Central Java PON sepak takraw training team. The data analysis technique used in this study is a descriptive statistical technique using SPSS by calculating percentage, mean, minimum value, maximum value and standard deviation. The results of the study showed that there was 1 component of physical condition that was in the very good category, namely agility, 2 components of physical condition were in the good category, namely abdominal muscle strength and aerobic endurance, and 2 components of physical condition were in the poor category, namely leg muscle explosiveness and speed. Thus, it can be concluded that the average professional score of the physical condition of PON athletes in Central Java 2024 is in the medium category.